The possible effects of irrigation schemes and irrigation methods on water budget and economy in Atatürk dam of South-Eastern Anatolia region of Turkey - Demir H.; Erkan A.Z.; Baysan N.; Bilgen G.K. (Technological perspectives for rational use of water resources in the Mediterranean region, 2009)
The South-eastern Anatolia Project (GAP) is consisting of 13 sub-projects in the river basins of Euphrates and Tigris. The project has evolved over time and has become multi sectoral, integrated and human based on the sustainable regional development. Upon the fully completion of the project, 1.8 million hectares of land will be able to be irrigated in Euphrates and Tigris Basins through surface and underground water resources. From 1995 until now, 273.000 ha. of land have already been irrigated within the GAP Project. Roughly 739,000 ha. of this land will be irrigated from Atatürk Dam, the largest dam of GAP Project. At present, nearly 1/4 of this area is under irrigation. Some technological developments have been experienced in the Project area, as upstream controlled schemes having trapezoidal section, lined or unlined, or pressurized piped system; conventional or drip irrigation methods. The effects of those kinds of developments over water budget of irrigation schemes from Atatürk Dam have been studied. The data gathering from both 472,000 ha. of pumping irrigation and 267.000 ha. of gravity irrigation area is used in this study. Monthly plant water consumptions are determined through referenced plant water consumption gathered by GIS in association with plant growth index acquired from regional research studies. Irrigation module and annual total irrigation requirement are determined under different schemes and methods by means of monthly estimated plant water consumption rates. The contribution to the cost of energy generated by Atatürk Dam and to the cost of energy under pumping irrigation is determined.
2. MELIA Workshop Technological Perspectives for Rational Use of Water Resources in the Mediterranean Region, 2008/10/29-2008/11/02, Marrakesh (Morocco)